Answer:
x = -3h
x = -12
Explanation:
Given equation is
![(x)/(h)+1=-2](https://img.qammunity.org/2021/formulas/mathematics/college/zcua7723sywngfy1ckcolyyx7fp547qb6z.png)
To find the value of x in terms of h we will solve the expression to isolate x on one side of the equation.
by subtracting 1 from both the sides of the equation,
![(x)/(h)+1-1=-2-1](https://img.qammunity.org/2021/formulas/mathematics/high-school/ossfovi13e7o6l162kwsrwvhfd2upil1ne.png)
![(x)/(h)=-3](https://img.qammunity.org/2021/formulas/mathematics/college/ro7y13g1srfbkzycy2we2j3yj09q4yoltb.png)
Multiplying 'h' on both the sides of the equation,
![((x)/(h))* h = (-3)h](https://img.qammunity.org/2021/formulas/mathematics/high-school/9gx1jtv3aw42h426x2fyigfwejrihadx8x.png)
x = -3h
If h = 4,
x = (-3)(4)
x = -12